2022
DOI: 10.1002/acp.4005
|View full text |Cite
|
Sign up to set email alerts
|

Changing beliefs in repressed memory and dissociative amnesia

Abstract: In three studies, we examined whether beliefs in repressed memory and dissociative amnesia could be changed. Participants provided agreement ratings to statements related to repressed memory and dissociative amnesia. Then, they received a university course which included education on the science of memory. Following this, participants had to re-rate the statements. In Study 3, at Times 1 and 2, participants also received a case vignette on a therapy-induced recovered memory and rated several statements related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Hence, it is our opinion that the science of memory and the danger of suggestion should be standard teaching materials in training programs for mental health professionals. Such training programs might have the potential to make therapists more critical towards controversial topics such as repressed memory (Otgaar et al , 2022b; Sauerland and Otgaar, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is our opinion that the science of memory and the danger of suggestion should be standard teaching materials in training programs for mental health professionals. Such training programs might have the potential to make therapists more critical towards controversial topics such as repressed memory (Otgaar et al , 2022b; Sauerland and Otgaar, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the idea of repressed memory stands in contrast with a plethora of research showing that memories for trauma are typically easily retrievable (McNally, 2005). Also, according to the critics, claims of traumatic memory loss can be explained by other, more plausible explanations, such as lack of initial encoding of the traumatic event, normal forgetting and failures to disclose or remember previous discussions concerning the traumatic experience (McNally, 2003; Otgaar et al , 2022b; see also Mangiulli et al , 2021; Mangiulli et al , 2022).…”
Section: Dissociation Repression and Traumatic Memoriesmentioning
confidence: 99%
“…However, other scholars (mainly memory researchers) posited that these therapeutic interventions were suggestive, thereby increasing the likelihood that these recovered memories were in fact false memories. Furthermore, these scholars asserted that traumatic memories are not repressed but are actually well remembered and that failures to remember traumatic memories could be caused because of plausible alternative explanations such as a lack of disclosure or ordinary forgetting (Otgaar et al, 2019;Otgaar et al, 2022aOtgaar et al, , 2022b. This debate on the existence of repressed memory has also been termed the memory wars (Crews, 1995).…”
Section: The Debate On Repressed Memorymentioning
confidence: 99%
“…Although scientific evidence speaks against the existence of repressed memory, many people continue to harbour a strong belief in repressed memory (e.g. see for examples Dodier et al, 2019aDodier et al, , 2019bPatihis et al, 2014;Otgaar et al, 2022aOtgaar et al, , 2022b. In the current study, we examined potential cultural differences in believing in repressed memory.…”
Section: Introductionmentioning
confidence: 96%
“…Recent work has shown that memory wars still rage on ( Dodier, 2019 ; Otgaar et al, 2019 ; Battista et al, 2023 ), with similar opposing camps. However, it appears that the debates have shifted towards neuroscientific approaches, with some authors (e.g., Markowitsch and Staniloiu, 2013 ; Chechko et al, 2018 ; Dimitrova et al, 2021 ) suggesting the existence of brain biomarkers of dissociative amnesia (another way of calling repression, Otgaar et al, 2019 , 2023 ), while others have criticized the validity and lack of homogeneity of the results found in studies using brain imaging ( Otgaar et al, in press ). Closely associated with the topic addressed in our article, the debate has also shifted somewhat to something other than a repressed vs. false memory dichotomy.…”
Section: Introductionmentioning
confidence: 99%